Financial Decision-Making in the Age of Artificial Intelligence: A Systematic Literature Review - Muhammad Haris Saputra; Fitriati, Fitriaty (Future Science, 2025)
The development of artificial intelligence (AI) is fundamentally transforming how individuals, financial institutions, and regulators make financial decisions. In Indonesia, this transformation is visible in the use of AI for risk management, creditworthiness assessment, robo-advisory services, and the prediction of stock prices and indices. This article aims to systematically examine the role of AI in financial decision-making with a specific focus on the Indonesian context, combining national studies accredited in Sinta with international articles indexed in Scopus. The study employs a systematic literature review (SLR) of 20 articles published in recent years, including conceptual studies, systematic reviews, and empirical research based on market and customer data. The findings indicate that AI makes significant contributions in: (1) improving the accuracy of risk management and loss prediction, (2) expanding financial inclusion through innovative credit scoring schemes, (3) supporting investment decision-making via robo-advisors and capital market prediction models, and (4) shaping new, highly digital financial behaviours that nevertheless raise ethical, transparency, and algorithmic bias concerns. At the same time, there are challenges related to data quality, model transparency, consumer protection, and AI literacy among Indonesian financial actors.